MEKANISME GANTI RUGI DAN REHABILITASI DALAM TINDAK PIDANA PENCURIAN YANG DILAKUKAN ANAK DIBAWAH UMUR (Studi Putusan Pengadilan Negeri Cibinong No: 36/Pdt.G/2012/PN.Cbn.) - Dina Rahmawati; Burhanudin Burhanudin; Hidayatulloh Hidayatulloh (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2020)
The problem in this study is that the defendant who is underage committing a theft has been decided freely by the judge submitting compensation and rehabilitation because the defendant suffered material and immaterial losses in the Decision of the Cibinong District Court No: 36 / Pdt.G / 2012 / PN.Cbn . This study aims to understand how the compensation and rehabilitation mechanism of theft perpetrators has been dismissed freely. This study uses qualitative research methods using a normative approach. The results show that the convicted person has the right to claim compensation and rehabilitation, and compensation is directed at law enforcement or directed at the guilty party.Keyword : Compensation, Rehabilitation, Presumption not innocent.